Estructuración del proyecto de vinculación entre la carrera de gerencia y liderazgo de la Universidad Politécnica Salesiana con las pymes de la zona Quitumbe del sur de Quito - Rosero Melo, Daroma Alexandra (2010)
This research will build mechanisms of relationship between the UPS with the community, particularly the race of Management and Leadership and SMEs in the Quitumbe area south of Quito and determine the specific content for its implementation, which will impact on the improving management capacity of SMEs and to complete the theoretical and practical information for students career management and Leadership UPS.